Association study in eating disorders: TPH2 associates with anorexia nervosa and self-induced vomiting - Slof-Op 't Landt, Rita; Meulenbelt, I.; Bartels, M.; Suchiman, E.; Middeldorp, C. M.; Houwing-Duistermaat, J. J.; van Trier, J.; Onkenhout, E. J.; Vink, J. M.; van Beijsterveldt, C. E. M.; Brandys, M. K.; Sanders, N.; et al. (Genes, brain and behavior, 2011)
Twin studies suggest that genetic factors play a substantial role in anorexia nervosa (AN) and self-induced vomiting (SV), a key symptom that is shared among different types of eating disorders (EDs). We investigated the association of 25 single nucleotide polymorphisms (SNPs), capturing 71-91% of the common variance in candidate genes, stathmin (STMN1), serotonin receptor 1D (HTR1D), tryptophan hydroxylase 2 (TPH2) and brain-derived neurotrophic factor (BDNF), with AN and EDs characterized by regular SV. The first allele frequencies of all the SNPs were compared between a Dutch case group (182 AN, 149 EDs characterized by SV) and 607 controls. Associations rendering P-values < 0.05 from this initial study were then tested for replication in a meta-analysis with two additional independent ED case-control samples, together providing 887 AN cases, 306 cases with an ED characterized by SV and 1914 controls. A significant effect for the minor C-allele of tryptophan hydroxylase 2 rs1473473 was observed for both AN [odds ratio (OR) = 1.30, 95% CI 1.08-1.57, P < 0.003] and EDs characterized by SV (OR = 1.52, 95% CI 1.28-2.04, P < 0.006). In the combined case group, a dominant effect was observed for rs1473473 (OR = 1.38, 95% CI 1.16-1.64, P < 0.0003). The meta-analysis revealed that the tryptophan hydroxylase 2 polymorphism rs1473473 was associated with a higher risk for AN, EDs characterized by SV and for the combined group.